Factors influencing the intention of trainee special education teachers to integrate assistive technology into teaching students with disabilities in the United Arab Emirates - Maxwell Peprah Opoku; Hala Elhoweris; Najwa Alhosani; Ashraf Mustafa; Thara Alkhateri; William Nketsia (Heliyon, 2023)
Technology has been incorporated into the educational systems of many countries as a teaching and learning tool. Contemporary discourse has focused on how to prepare teachers to utilise technology in their teaching practice. Although most pre-service elementary school teachers in the United Arab Emirates are women, studies have not yet investigated their acceptance of or preparedness to use technology in the classroom. Therefore, it is necessary to investigate whether the training provided to pre-service special education teachers equips them with sufficient skills to support students with disabilities. The present study used the technology acceptance model (TAM) as a theoretical lens to examine the factors that impact female pre-service special education teachers' intention to incorporate assistive technology (AT) in teaching students with disabilities. A survey based on TAM was used to collect data from 138 participants and test four study hypotheses. Regarding data analysis, SPSS and AMOS version 28 software were used to conduct exploratory factor, confirmatory factor and path analyses. Two of the four hypotheses were supported. The results provide support for the four-factor TAM structure, with two predictors – perceived ease of use and computer self-efficacy – supporting pre-service teachers’ intention to use AT to teach students with disabilities in the classroom. Teacher educators and policymakers should consider the TAM construct when preparing pre-service teachers to effectively support all students. Specifically, teacher development and stakeholder engagement with AT resources are needed to optimise the learning of children with disabilities.